Estrogen-Mitochondrial Interactions in Cellular Resilience: Biological Implications for Female Military Personnel - Cecilia Miranda; Syahrul Tuba; Leonardo Daniel Palmaro; Nadya Theresia Sibarani (CV. Wadah Publikasi Cendekia, 2026)
Military operations expose personnel to intense physiological and psychological stressors that can increase allostatic load and impair mitochondrial function. Estrogen, particularly 17β-estradiol, plays a crucial role in maintaining cellular homeostasis through the regulation of mitochondrial activity. This systematic narrative review aimed to examine estrogen–mitochondrial interactions as a biological basis for female cellular resilience under operational stress. A literature search was conducted using PubMed, Scopus, and ScienceDirect databases for publications from 2004 to 2024. A total of 44 eligible articles were qualitatively analysed. The findings indicate that estrogen modulates mitochondrial function through ERα, ERβ, and GPER signalling pathways. Estrogen promotes mitochondrial biogenesis via the PGC-1α/NRF-1/TFAM pathway, supports mitochondrial dynamics through MFN2 and OPA1 proteins, enhances antioxidant defence by increasing MnSOD and catalase activity, and suppresses apoptotic processes. In addition, recent evidence suggests that estrogen contributes to the regulation of mitophagy and the maintenance of mitochondrial DNA (mtDNA) stability. In conclusion, estrogen–mitochondrial interactions play a critical role in supporting metabolic and neurocognitive resilience in women. These findings provide a scientific foundation for the development of gender-specific health strategies aimed at optimising female performance and adaptability in demanding military environments.